Preliminary studies of photolysis and TiO2-montmorillonite-immobilised photocatalysis processes for the degradation of organic pollutants in water treatment - Pamuła, Justyna; Karnas, Magdalena; Styszko, Katarzyna (Geology, Geophysics and Environment, 2022)
Organic compounds are the most diverse group of contaminants. The largest anthropogenic source of these contaminants in water is municipal and industrial wastewater. One of the indicators of surface water pollution is biological oxygen demand (BOD). Purifying water from organic micropollutants is a serious challenge and requires the development of newer and more effective methods. The removal of such contaminants is most effective only in advanced oxidation processes (AOP), which include UV photolysis and photocatalysis. The presented results are from preliminary research to evaluate the effectiveness of water treatment by ultraviolet (UV) photolysis and photocatalysis. Treatment efficiency was evaluated on the basis of changes in the BOD index before and after the advanced oxidation process of raw water. The values of the BOD5 index determined in accordance with PN-EN 25813:1997. The exposure time of the samples was a maximum of 60 minutes. The tested material was water samples taken from the Rudawa River, which is one of the drinking water sources for Krakow. The initial BOD5 value (expressed as concentration of O2) for all samples was about 8 mg/L but it has decreased to over 2 mg/L due to AOP processes. This means that after an hour, more than 75% of organic compounds present in the raw water were removed. For photocatalysis (TiO2-MMT), the exposure time of the samples was a maximum of 35 minutes. Water samples taken from the Rudawa River were also used as test material. The initial BOD5 value for all samples was about 9 mg/L but it has decreased to about 4 mg/L due to the photocatalysis process. This means that after 35 minutes, 55% of the organic compounds present in the raw water were removed.